Book Reviews (Rev. Anal. Numér. Théor. Approx., 2000)
Book reviews for:Beresford N. Parlett, The Symmetric Eigenvalue Problem, Classics in Applied Mathematics 20, SIAM, Philadelphia, 1998, XXIV+398 pp., ISBN 0-89871-402-8. Reviewed by E. Catinas.Stephan Kaufman, A Crash Course in Mathematica, Birkhauser Verlag, Basel-Boston-Berlin, 1999, 200 pp., ISBN 3-7643-6127-7 and 0-8176-6127-1. Reviewed by S. Cobzas.The Maz'ya Anniversary collection, J. Rossmann, P. Takac, G. Wildenhaim (Editors), Vol. l, On Maz'ya world in Functional Analysis, Partial Differential Equations and Applications, XII+364 pp., ISBN 3-7643-6201-4; Vol. 2, Rostock Conference on Functional Analysis, Partial Differential Equations and Applications, XVl+352 pp., ISBN 3-7643-6202-2; Birkhauser Verlag, Boston-Basel-Berlin, 1999. Reviewed by S. Cobzas.Nicholas J. Higham, Handbook of Writing for the Mathematical Sciences, Second Ed., Philadelphia, 1998, XV+302 pp., ISBN 0-89871-420-6. Reviewed by E. Catinas.Sidney I. Resnick, A Probability Path, Birkhauser, Boston-Basel-Berlin, 1998, XII+453 pp., ISBN: 0-8176-4055-X, 3-7643-4055-X. Reviewed by P. Blaga.Martin Schechter, Linking Methods in Critical Point Theory, Birkhauser, Boston-Basel-Berlin, 1999, XVIII+294 pp., ISBN 0-8176-4095-9. Reviewed by R. Precup.C. T. Kelley, Iterative Methods for Optimization, Frontiers in Applied Mathematics 18, SIAM, Philadelphia PA, 1999, XV+180 pp., ISBN 0-89871-433-8. Reviewed by E. Catinas.